Optimal iterative learning control design for continuous-time systems with nonidentical trial lengths using alternating projections between multiple sets - Zhuang, Zhihe; Tao, Hongfeng; Chen, Yiyang; Oomen, Tom; Paszke, Wojciech (1975- ); Rogers, Eric
Iterative learning control (ILC) applies to systems that repeat the same finite duration task repeatedly. Each repetition is usually termed as a trial, and the associated duration is called the trial length. Once a trial is completed, all information is available for use in updating the control input for the subsequent trial. The vast majority of the currently available designs demand a strictly identical trial length.
Keywords: iterative learning control; alternating projection; nonidentical trial length; continuous-time system; accelerated design